Empowering the Economy of Plasma Farmers of “PT Arda and Omid Farm” through Feed-Entrepreneur Activities in Pangpong Village - Kusmartono, Kusmartono; Bisri, Mohammad; Muluk, Mujibur Rahman Khairul; Muttaqin, Syariful; Ndaru, Poespitasari Hazanah; Kartika, Aprilia Dwi; Herlina, Herlina (Journal of Innovation and Applied Technology, 2025)
The Doktor Mengabdi Program in Pangpong Village aims to empower small-scale plasma farmers under PT Arda and Omid Farm by developing a self-sufficient livestock community. This initiative enhances economic growth through feed entrepreneurship and modern cattle farming. The program benefits 29 partnered farmers managing 58 beef cattle. It includes extension services, training in efficient feed production, and practical workshops on improving feed quality. Farmers also receive education on livestock management and marketing strategies to support sustainable businesses. Regular field visits ensure effective adoption of new practices, while profitability analysis evaluates economic impacts. Key outcomes include improved farmer expertise in feed management, increased feed quality and quantity, and the establishment of profit-oriented cattle farming. A major achievement is the development of a Mini Feedmill, supporting sustainable feed production and long-term livestock farming success. This program significantly boosts farmer income and strengthens the local cattle industry.